Model Wakaf Energy (Solar Panel) terhadap Isu Perubahan Iklim - Nur Khayin Muhdlor (Jurnal Syntax Admiration, 2024)
Reducing the amount of gases such as carbon dioxide and methane released into the atmosphere is one of the causes of climate change, which is from actions such as burning fossil fuels, industrial processes, and agricultural practices using renewable energy, such as solar energy. The purpose of this study is to evaluate the model in depth of energy waqf (solar panel) on the issue of climate change. The data of this study was obtained through a literature study and evaluated in three steps: data reduction, data distribution, and conclusion drawn. The results of the study show that the waqf energy model (solar panel) can reduce greenhouse gas emissions. This is because solar power plants built with waqf funds can produce safe electrical energy and do not emit greenhouse gases. Solar power plants built with waqf funds can be used to meet the needs of the community, such as households, SMEs, and industries. This can reduce people's dependence on fossil energy, which is an energy source that produces greenhouse gas emissions. In addition, the energy waqf model (solar panels) can also generate economic and social benefits for the community.